Virtual nutrition education for people affected by Parkinson’s disease - Brenes, Priscilla (Kansas State University, 2021)
Parkinson's disease is a progressive movement condition and, after Alzheimer's disease, the second most common neurodegenerative disease. Parkinson's disease has no proven cure. However, efforts are being made to improve the quality of life of people with Parkinson’s. Quality of life encompasses a variety of domains, including nutritional health. The progression and severity of Parkinson's disease is linked to nutrient intake and nutrition status. The period and severity of Parkinson's disease are linked to nutrient intake and nutrition status. Malnutrition, digestive problems, and eating problems impair muscle strength, mass, and cramps, reducing equilibrium and speeding up the progression of Parkinson's disease. A lack of nutrition can increase one's dependency on everyday activities, lowering the person's quality of life. Scientific publications on the basic benefits of nutrition education services in this population are scarce. Self-management services, which seek to enhance quality of life, assist participants in coping with Parkinson's disease diagnosis while also improving communication and mental health. Some of these initiatives can provide nutrition; however, there is insufficient data to report on the effects. It is essential to consider what knowledge people with Parkinson's disease are interested in and their needs before developing a nutrition self-management education program. Focus groups can assist with gathering this knowledge to create an effective program. This study aimed to increase nutrition knowledge and improve quality of life through virtual nutrition education to people with Parkinson’s disease and their care partners. This experimental design was a mixed-methods approach, using focus groups to determine topics of interest and pre- and post-self-report data to assess program effectiveness and quality of life. The study’s nutrition education portion was divided into six modules and was eight weeks in duration. Weeks one and eight were for data collection. A total of 28 people enrolled in the virtual program, and fifteen participants completed the pre-and post-surveys (54% completion rate). Participants were at risk of malnutrition. However, according to their intake report, their total consumption of macro-and micronutrients increased. Additionally, even though quality of life did not have a statistically significant change, six out of 12 participants improved their quality of life scores. Additionally, participants expressed how the program led them to be more aware of healthy eating, gut health, hydration, food-medication interaction, and constipation. In conclusion, this program was tailored specifically to the knowledge needs of the participants and this population. This virtual program was useful, worthwhile, engaging, and helpful for the participants. Additionally, the program was a resource that helped improve quality of life by providing support through nutrition knowledge.
Keywords: Parkinson's disease; Nutrition education; Virtual education; Elderly education